Immediate social and economic impacts of a major oil spill on Brazilian coastal fishing communities. (March 2021) - de Oliveira Estevo, Mariana; Lopes, Priscila F.M.; de Oliveira Júnior, José Gilmar Cavalcante; Junqueira, André Braga; de Oliveira Santos, Ana Paula; da Silva Lima, Johnny Antonio; Malhado, Ana Claudia Mendes; Ladle, Richard J.; Campos-Silva, João Vitor
Abstract: In August 2019, a major oil spill hit nine Brazilian coastal states, affecting marine ecosystems and fishing communities. In this study, we assess the immediate social and economic impacts of this oil spill on fishing communities of the northeast coast. We conducted semi-structured interviews and focal meetings with 381 fishers and shellfish gatherers to understand the perceived socioeconomic impacts on different types of fishing. We also obtained information on fish consumption after the oil spill, which we compared with data prior to the oil spill from the same communities. Sales decreased by more than 50% for all types of fishing, strongly impacting local income generation. These communities, which are already social-ecologically vulnerable, have had their subsistence, food security and cultural maintenance strongly compromised. We argue that there is a clear need for coordinated state interventions to mitigation the impacts, considering it's environmental, social, economic, human health and political dimensions. Highlights: A huge oil spill arrived in Brazilian coast, dramatically impacting biodiversity and local communities; Brazilian government is still lenient, and source of the spill and its impacts are still a mysterious; There is a huge impact on seafood trade, including a strong decline in sales and prices; We recommend and urgent integrated strategy to attenuate this environmental and socioeconomic tragedy.